PENGARUH LINGKUNGAN KERJA, KOMUNIKASI, DAN STRES KERJA TERHADAP KEPUASAN KERJA KARYAWANSOUTHLINKS COUNTRY CLUB BATAM - Vinla Samwita; Hikmah, Hikmah (SCIENTIA JOURNAL, 2022)
The purpose of this study was to determine whether the work environment, communication and job stress affect job satisfaction at Southlinks Country Club Batam. This research was conducted using quantitative techniques. The population used consisted of 145 respondents at Southlinks Country Club Batam. The research sample used as many as 152 respondents at Southlinks Country Club Batam using the slovin formula. Questionnaires were used as a data collection technique. By using SPSS 25 software, data analysis techniques include descriptive statistical tests, data quality tests, classical assumption tests, influence tests, and hypothesis testing. Based on the results of multiple linear regression, the work environment (X1) has an effect of 0.164 or 16.4% on job satisfaction (Y) at Southlinks Country Club Batam, communication (X2) has an effect of 0.368 or 36.8% on job satisfaction (Y) at Southlinks Country Club Batam and work stress (X3) have an effect of 0.202 or 20.2% on job satisfaction (Y) at Southlinks Country Club Batam. Work environment factors, communication and work stress affect job satisfaction (Y) at Southlinks Country Club Batam by 64.7% according to the data of the coefficient of determination (R2). Based on the results of hypothesis testing, it was found that the work environment, communication and work stress had a positive and significant effect partially or simultaneously on job satisfaction (Y) at Southlinks Country Club Batam.